Ionizing radiation exposure is still increasing in Crohn's disease: Who should be blamed?. (October 2015) - Magro, Fernando; Coelho, Rosa; Guimarães, Luís S.; Silva, Marco; Peixoto, Armando; Lopes, Susana; Macedo, Guilherme
Abstract Background and aim. Crohn's disease (CD) patients undergo many radiological studies employing ionizing radiation for diagnosis and management purposes. Our aim was to assess the total radiation exposure of our patients over the years, to estimate the risk factors for exposure to high doses, and to correlate radiation exposure to immunosuppression. Methods. The cumulative effective dose of radiation (CEDR) was calculated multiplying the number of imaging studies by the effective dose of each examination. Results. A total of 451 patients with CD (226 female) were followed during 11.0 years (interquartile range [IQR]: 6.0–16.0), with 52.1% of the patients being classified with penetrating (B3) and 38.6% being steroid-dependent. About 16% were exposed to high-radiation dose levels (CEDR >50 mSv) and 4% were exposed to CEDR >100 mSv. The mean CEDR between age 26 and 35 years was 12.539 mSv and a significant dose of radiation (over 50 mSv) was achieved at a median age of 40 (IQR: 29.0–47.0). Abdominal-pelvic computed tomography scan was the examination that contributed the most for CEDR. Patients with B3 phenotype, previous surgery, azathioprine, and anti-tumor necrosis factor (TNF)-α therapy were exposed earlier on the course of the disease to CEDR >50 mSv (p < 0.001). The value of CEDR in the patients under immunosuppression mainly increased in the first year of immunosuppression. Conclusion. Penetrating phenotype, abdominal surgery, steroid resistance or steroid dependence, and treatment with anti-TNF-α and azathioprine were predictive factors for high CEDR. It was also demonstrated that immunosuppression and anti-TNF-α treatment were followed by a sustained increment of radiation exposure and that a significant dose of radiation was achieved <40 years of age.